Enrichment Opak Kelor Ikan Modifikasi dan Dampaknya pada Anak Stunting di Kabupaten Lombok Utara - Fifi Luthfiyah; Susilo Wirawan (Poltekkes Kemenkes Mataram, 2020)
Stunting prevalence (5-12 years) is 34.4% which is the highest number in the NTB region compared to 10 other regencies / cities (NTB Province average of 14.9%) (Riskesdas, 2013). Fish Kelor Opak (OKI) is one of the traditional foods that can be strived to reduce Stunting (very short) in nutrient-prone groups in North Lombok Regency. In the three years of Health Intervention Research, problems still arise that quite disturb the sustainability of OKI consumption. There are not yet many traditional Opak craftsmen who produce Fish Kelor Opac (OKI) because of the ability of the craftsmen to provide raw materials and need modification of the materials, so that people like it. The purpose of this study was to modify Fish Moringa Opaque and its effects on stunting children. Descriptive observational method with emphasis on making Moringa Fish Opaque with different fish ingredients. The best products are given to children stunting. The results showed that modified Fish Opaque Moringa was made which had better taste, shape and texture than before. There is a difference in BB in children with stunting + OKI (P1) before and intervention is 2.07 kg, compared to P0 of 0.56 kg and There is a difference in TB in children with stunting + OKI (P1) before and after the intervention of 0.54 cm compared to P0 of 0.4 cm.